The Analysis and Design of System Information in KPR Decision Making Using AHP and SAW methods (Study Case: PT. Bintang Baru) - Nanda Aristantiyo Meylinda; Benny Daniawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2018)
In this era, the development of information technology is so fast that it cannot be looked away. This development of information technology is going to affect many kinds of fields, including developer. The point of this development is to help the work done by the people become easier. One of its benefit is in decision making. Decision mistakes is one of the general problems that usually happened in decision making. A system will be made with the purpose to ease the decisions making process through methods. The methods are Analytical Hierarchy Process (AHP) as weight calculation and Simple Addictive Weighting (SAW) as an alternative calculation media. In this system there are 5 criteria which are: non-fixed income, living cost, age, SPT Pph Ps. 21 for credit and paycheck. There are 11 alternative that can be used as a consideration for the manager. By using AHP method which has a consistent ratio reaching 96,62% and SAW, the selection process is going to be faster than it used to be, helping the Manager in making the decision also lessen the use of space and paper